Reciprocity and Workers' Tastes for Representation - Uwe Jirjahn; Vanessa Lange (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
Using unique survey data from the German Socio-Economic Panel, this study examines the influence of reciprocal inclinations on workers' sorting into codetermined firms. Employees with strong negative reciprocal inclinations are more likely to work in firms with a works council while employees with strong positive reciprocal inclinations are less likely to work in such firms. We argue that these findings conform to hypotheses derived from the experimental literature. Moreover, the results showstriking gender differences in the relationship between reciprocity and taste for representation. These differences can be partially explained by gender-specific differences in the average degree of labor force attachment.
Keywords: D3; J52; J53; M50; 330; Works council; negative reciprocity; positive reciprocity; sorting; gender; Arbeitskräfte; Präferenztheorie; Betriebsrat; Austauschtheorie; Geschlecht; Deutschland